Turkey : Corporate Sector Impact Assessment Report - World Bank (Washington, DC, 2013)
In February 2001, Turkey was hit by its deepest economic and financial crisis since World War II, prompting a severe decline in business activity. The adverse effects of the crisis were felt throughout the economy-starting in the public sector, spreading to the financial sector, and, causing increasing distress in the real sector. To restore growth and return companies to profitability, Turkey urgently needs to implement a comprehensive corporate restructuring program. Moreover, simultaneous resolution efforts are needed in cases where corporate distress is creating distress for financial institutions. The report explores the significance and depth of the crisis, which includes an analysis of corporate perceptions of the crisis, and corporate distress. Several factors will limit the ability of Turkish financial institutions to resolve distress among corporate borrowers. Weak insolvency and foreclosure procedures may encourage a race to seize collateral, inhibiting orderly workouts of non-liquid but viable companies. Small, capital-weakened banks could be particularly nettlesome in corporate workout negotiations. Banks need to recognize that such workouts can reduce non-performing loans, and restore their clients' creditworthiness. In addition, the Banking Regulation and Supervision Agency needs to develop policies that encourage banks to participate in voluntary workouts. Drawing on various models worldwide, recommendations suggest: resolution strategies to help banks and firms resolve their "mutual hostage'' dilemma; policy changes for the Government to facilitate resolution and attract foreign direct investment; and, financing measures to help firms overcome the credit crunch. Recommendations are also split between short-term measures, and medium-term measures - these medium-term measures are crucial because corporate distress will likely continue well beyond the initial macroeconomic recovery, while many of these measures, such as facilitating foreign direct investment and improving the management and transparency of large corporate groups, will have long-lasting effects.